Control system dynamics - Clark, Robert N. (Cambridge University Press, 1996)
Automatic control systems have become essential features in virtually every area of technology, from machine tools to aerospace vehicles. This book is a comprehensive, clearly written introduction to automatic control engineering. The author begins with the fundamentals of modelling mechanical, electrical, and electromechanical systems in the state variable format. The emphasis is on classical feedback control theory and design, and their application to practical electromechanical and aerospace problems. Following a careful grounding in classical control theory, the author introduces modern control theory, including digital control and nonlinear system analysis. Over 230 problems help the reader apply principles discussed in the text to practical engineering situations. Engineering students and practising engineers will find all they need to know about control system analysis and design in this valuable text.